Unravelling induced resistance in strawberry: distinct metabolomic signatures define cultivar-specific resistance to Botrytis cinerea - Murena, Chiara; Pastor, Victoria; Fernandes, Tânia R.; Carvalho, Susana M. P.; Luna, Estrella (Frontiers in Plant Science, 2025)
IntroductionBotrytis cinerea is a major pathogen in strawberry, and sustainable alternatives to fungicides are needed to manage this disease. Induced resistance (IR) through chemical elicitors represents a promising strategy, but the effectiveness of such compounds remains poorly understood in commercial strawberry (Fragaria × ananassa) cultivars.MethodsIn this study, we evaluated the efficacy of repeated applications of five elicitors (i.e., β-aminobutyric acid (BABA), (R)-β-homoserine (RBH), indole-3-carboxylic acid (I3CA), jasmonic acid (JA), and salicylic acid (SA)) in three strawberry cultivars (Rowena, Soraya, and Durban).ResultsBABA and RBH significantly reduced B. cinerea lesion sizes in Rowena and Soraya, while Durban showed no induced resistance to the elicitors. Untargeted metabolomic profiling of Rowena and Soraya revealed cultivar-specific responses to elicitor treatment and infection, with distinct patterns of metabolite accumulation under both mock- and B. cinerea-inoculated conditions. RBH in Rowena and BABA in Soraya induced the most extensive priming-associated metabolic reprogramming, including enrichment of amino acid, nucleotide, and secondary metabolite pathways such as flavonoids and phenylpropanoids. Significantly, none of the elicitors negatively affected plant growth, flowering, or fruit set.DiscussionThese results demonstrate that the effectiveness and mechanism of IR in strawberry depend on both the elicitor and the cultivar, providing new insights into the metabolomic basis of priming with implications for sustainable disease management in strawberry cultivation.